WHEN VARIABLES ARE NO LONGER SUFFICIENT: AN INTERPRETATIVE PHENOMENOLOGY OF THE VOLCANIC TOURISM EXPERIENCE IN EAST JAVA - Leonard Adrie Manafe (JURNAL ILMIAH EDUNOMIKA, 2026)
Quantitative research on tourist behavior in Indonesia has repeatedly found that psychological variables such as attitude and subjective norm explain only a small share of the variance in visitation intention, suggesting that a substantial part of the tourist experience escapes measurement. This study uses Heideggerian interpretive phenomenology to explore the lived experience of ten tourists at Ijen Crater, Mount Bromo, and Madakaripura Waterfall. Drawing on in-depth interviews structured around van Manen's four existential dimensions; lived space, lived body, lived time, and lived relation; thematic analysis shows that the attitudes captured in survey instruments originate in pre-cognitive bodily reactions: goosebumps and silence that recur across all demographic groups. Subjective norms appear weak in statistical models not because social influence is absent, but because it has been internalized so deeply that tourists no longer perceive it as external. Physical discomfort becomes social capital, solitude amid crowds becomes a space for existential reflection, and revisit intention forms ontologically during the experience itself rather than through post-visit rational evaluation. We introduce the concept of "transformation that begins before it ends" to describe this intention-formation mechanism, which the Theory of Planned Behavior cannot account for. The study demonstrates the methodological value of interpretive phenomenology in explaining non-significant quantitative findings and offers practical guidance for developing experience-based tourism attentive to tourists' emotional complexity and personal transformation.